Probabilitas Syariatisasi Negara Paska Orde Baru: Berkaca dari Strategi Kelompok Islamis Memperjuangkan Pengesahan RUU APP - Al Akbar, Nuruddin (The Sociology of Islam, 2013)
The article attempts to examine the Islamist group's efforts in the fight for the implementation of Islamic law in the frame issues that tend to be accepted by society in general. Framing the issue in such a manner intended to create broad support for Islamist agenda initiated. This article focuses the discussion on the APP bill case as a clear example of this strategy to frame the issue of Islamist groups to fight for their interests. This study is motivated from the debate among academics about the probability of syariatization of state in post-New Order era. Some people who can be termed as the skeptics, believes that the probability of syariatization is very small, because the power of the Islamists deemed not strong enough to fight for such agenda. On the other hand, there are also other camps that have different perceptions, which can be termed as the optimists. This camp believe that in post-New Order era, Islamist forces are so great and they are slowly transforming Indonesia towards an Islamic state in various ways. The article attempts to come out of the debate while providing an alternative perspective to understand the probability of syariatization of the state. The findings of this article indicate that the probability of the state is highly dependent on how Islamist groups are able to frame the issues that can be accepted and supported by the wide range of people. RUU APP-related cases, the Islamists were able to convince a wide audience about the need of syariatization, through an issue of morality. The use of the discourse of morality by the Islamists were able to bring the support of moderate Muslims such as Muhammadiyah and Nahdlatul Ulama, even other group like Aliansi Selamatkan Anak Indonesia, which is actually not based on Islamic ideology Kata Kunci: Syariatisasi Negara, Islamis, RUU APP.